Unveiling six novel bacterial strains for fipronil and thiobencarb biodegradation: efficacy, metabolic pathways, and bioaugmentation potential in paddy soil - Faridy, Nastaran; Torabi, Ehssan; Pourbabaee, Ahmad Ali; Osdaghi, Ebrahim; Talebi, Khalil (Frontiers in Microbiology, 2024)
Soil bacteria offer a promising approach to bioremediate pesticide contamination in agricultural ecosystems. This study investigated the potential of bacteria isolated from rice paddy soil for bioremediating fipronil and thiobencarb, common agricultural pesticides. Six strains, including both single isolates and their mixture, efficiently degraded these pesticides at high concentrations (up to 800 µg/mL). Enterobacter sp., Brucella sp. (alone and combined), and a mixture of Stenotrophomonas sp., Bordetella sp., and Citrobacter sp.effectively degraded fipronil and thiobencarb, respectively. Notably, a single Pseudomonas sp. strain degraded a mixture of both pesticides. Optimal degradation conditions were identified as a slightly acidic pH (6-7), moderate pesticide concentrations (20-50 µg/mL), and a specific inoculum size. Bioaugmentation assays in real-world paddy soils (sterile/nonsterile, varying moisture) demonstrated that these bacteria significantly increased degradation rates (up to 14.15-fold for fipronil and 5.13-fold for thiobencarb). The study identifies these novel bacterial strains as promising tools for bioremediation and bioaugmentation strategies to tackle fipronil and thiobencarb contamination in paddy ecosystems.